Yield Surfaces and Criteria of Plastic Yielding for a Strain Hardening Material. Part 1. Experimental Study - Miastkowski, J.; Szczebiot, R. (Engineering Transactions, 2001)
The paper presents the results of experimental investigations of yield surfaces and plastic yield criteria for an aluminium alloy under complex loading. Experiments were performed on flat specimens (cut out of a sheet of metal) under uniaxial tension or compression. The proposed methodology has allowed to determine simultaneously two characteristic sections of the yield load surfaces. The first of these sections lies in the region of tensile stress while the second one is within the compressive stress area. Then, these two sections have enabled us to describe the position and dimensions of the whole yield surface in the stress space. Tests were carried out at first for the material in the initial state and then in three other states of this material obtained under different plastic prestrains. Such a procedure allowed us to determine the quantitative changes in the yield surfaces dimensions and the position of their centres as a function of plastic prestrains.